(untitled) (Journal of Engineering, 2023)
This study focused on two areas in AL-Najaf city, AL-Ruhbah and Al-Haydariyah regions because of the importance and widespread use of groundwater in these areas. The two areas were compared quantitatively and qualitatively. For the quantitative approach, the GMS software was used in conjunction with the GIS software to simulate the groundwater flow behavior. The solid model for both areas was created, the geological formation was determined, and the hydraulic properties were identified using GMS software. To test the quantity of groundwater in both areas, the wells have been redistributed to a distance of 2000 m between them, and a period of 1000 days was chosen. When a discharge of 10 l/s and operation times of 4, 8, and 12 h/d were chosen for the AL-Ruhbah area, the maximum drawdown for all cases was equal to 18.04 m, whereas for Al-Haydariyah, when 5 l/s was chosen, the maximum drawdown was 0.81, 2.56, and 8.13 m, respectively. Field measurement and experimental laboratory tests were conducted to identify the type of water quality in the study areas. TDS, WQI, and SAR classification were employed to determine the type of groundwater. In both areas, groundwater was slightly to moderately saline. A piper diagram was also employed for the two regions to identify the water quality and it revealed that groundwater in the two studies cannot be used for drinking and can only be used for irrigation of plants that can withstand salty water.